ANALISIS FAKTOR-FAKTOR PENYEBAB KESULITAN BELAJAR MATEMATIKA SISWA KELAS IV SD NEGERI 21 PALEMBANG - Rosnatalia Nasution (JGK (Jurnal Guru Kita), 2023)
ANALYSIS OF  THE FACTORS CAUSING DIFFICULTY IN LEARNING MATEMATICS FOR CLASS IV STUDENTS OF SD NEGERI 21 PALEMBANG.  Learning difficulties are a situation where students are less able to face the demands that must be made in the learning process. So the process and results are not satisfactory. This learning difficulty is where students experience obstacles or disturbances in the learning process, the cause can come from students' internal and external factors. Internal factors include: student attitudes in learning, motivation, body health and external factors include: teacher variations in teaching, infrastructure, family environment. This study aims to determine the factors that influence the difficulty of learning matematic by the fourth grade students of SD Negeri 21 Palembang. This type of research uses qualitative research methods, the subjects used are fourth grade students. Data collection techniques are interviews, questionnaire,  and documentation. Then the results of the data obtained will be analyzed and presented in the form of a descriptive research report. The results of this study indicate that the difficulty of learning mathematic  in fourth grade students of SD Negeri 21 Palembang shows that many students still have difficulties in learning matematic. Most of the fourth grade students  were able to learn mathematic  well, but 7 of them had difficulty learning matematic. Keywords: Analysis; Learning Difficulty Factors; Matematics.